Trends in Myocardial Infarction risk by HIV status in two U.S. healthcare systems. - Alexandra N Lea; Asya Lyass; Leo B Hurley; Rachel Q Ehrbar; Taylor F Mahoney; Leila H Borowsky; Wei He; Jorge Plutzky; Virginia A Triant; Michael J Silverberg (PLoS ONE)
People with HIV have a higher risk of myocardial infarction (MI) compared with people without HIV. Real world evidence on whether the increased burden of MI in people with HIV is sustained over time is essential for understanding cardiovascular disease (CVD) patterns, optimizing management, and identifying unmet needs. To help fill this gap, we completed a cohort study of people with HIV and propensity matched people without HIV in two distinct US-based integrated healthcare systems (Kaiser Permanente Northern California and Mass General Brigham). Electronic health records were assessed for association of HIV status on MI risk in two calendar eras defined by baseline year: 2005-2009 and 2010-2017, with maximum 5-year follow-up, through 2020. Cox proportional hazards models were used to obtain adjusted hazard ratios (HR) for HIV status on MI risk overall and by cohort. Adjusted models controlled for demographics and traditional CVD risk factors. We included 9,401 people with HIV (78 with MI) and 29,418 people without HIV (204 with MI). In adjusted models, the HR for MI in people with HIV was 1.10 (95% CI, 0.76, 1.60) for years 2005-2009 and 1.66 (95% CI, 1.15, 2.39) for years 2010-2017 compared with people without HIV, with a corresponding P-interaction between HIV status and calendar era of 0.12. Differences were largely due to decreases in MI risk for people without HIV. The magnitude of HRs by calendar era was consistent across models stratified by cohort. Results showed an increased MI risk persisted among people with HIV in recent years relative to people without HIV, even as CVD rates are decreasing in the general population. In light of known HIV-specific CVD risk factors, continued surveillance for MIs is merited.